Changing Cultural Landscapes under the Impact of Exile, Diasporas and Return Migration - Roniger, Luis (Araucaria, 2024)
This article discusses the impact of territorial displacement on Argentina, Chile, Paraguay and Uruguay during the cycle of dictatorships and democratization of the late twentieth century and early twenty-first century. It points out the complexities and different forms of exile, expatriation and migration which these societies experienced, while asserting that exile could not be undone fully with democratization, as many of those who left did not come back, others left in new waves of expatriation, and even those who did return could not resume what had been left behind. Yet, the experience of living elsewhere broadened the social, political and cultural perspectives. Whether returning or not, or becoming sojourners, many individuals who left during the dictatorship made substantial contributions to the societies of origin in domains as varied as politics, arts and letter, science, the publishing industry, education, the state apparatus and the economy. Illustrations of such varied impact are presented.